Information technology in librarianship [electronic resource] : new critical approaches - Buschman, John; Leckie, Gloria J. (Westport, Conn : Libraries Unlimited, 2009)
The ground - both in terms of technological advance and in the sophistication of analyses of technology - has shifted. At the same time, librarianship as a field has adopted a more skeptical
1. Introduction : information technologies and libraries : why do we need new critical approaches? -- 2. Critical theory of technology : an overview -- 3. Surveillance and technology : contexts and distinctions -- 4. Cycles of net struggle, lines of net flight -- 5. A quick digital fix? : changing schools, changing literacies, persistent inequalities : a critical, contextual analysis -- 6. Theorizing the impact of ITon library-state relations -- 7. The prospects for an information science : the current absence of a critical perspective -- 8. Librarianship and the labor process : aspects of the rationalization, restructuring, and intensification of intellectual work -- 9. "Their little bit of ground slowly squashed into nothing" : technology, gender, and the vanishing librarian -- 10. Children and information technology -- 11. Open source software and libraries -- 12. Technologies of social regulation : an examination of library OPACs and Web portals -- 14. Libraries, archives, and digital preservation : a critical overview -- 15. Conclusion : just how critical should librarianship be of technology?
Description based on print version record
Includes bibliographical references and index
Keywords: Libraries -- Information technology